Gavril Radomir (1014–1015) and John Vladislav (1015–1018), rulers of the Bulgarian state in the Byzantine sources - Leszka, Mirosław Jerzy (Balcanica Posnaniensia. Acta et studia, 2019)
The article concerns the image of the Bulgarian tsars: Gavril Radomir and John Vladislav, who resisted the emperor Basil II for over three years after the death of tsar Samuel. According to the author, they did enjoy much attention of the Byzantine historians. On the one hand, it was due to the briefness of the reigns of the aforementioned tsars’, on the other, because of the conviction that the outcome of the conflict between the Empire and Bulgaria of Cometopulis had been decided earlier - during the bloody war with Samuel, who certainly was considered a character of much higher stature than his successors.